Influence of complexing agent in Tl-containing sol-gel derived precursor on critical temperature enhancement of Tl0.5Pb0.5Sr1.8Yb0.2 CaCu2O7 superconductor - Marsom E.S.; Yahya A.K.; Hamid N.A.; Awang Z.; Hamadneh I. (2023)
Superconducting oxide ceramics of composition Tl0.5Pb0.5Sr1.8Yb0.2CaCu 2O7 was prepared by using a single-step sol-gel process using two different complexing agents (tartaric acid and citric acid). The effect of the complexing agents (0.0-11.0% (w/w %)) on superconductivity of the samples were studied. It was found that the values of critical temperature, Tc zero, was enhanced from 88 K (for the sample without any complexing agents) to 95 K (for sample with 11 w/w % tartaric acid) and 97 K (for sample with 11 w/w% citric acid). SEM analysis showed formation of ultra-fine grains with 1-2 ?m average grains size for the sample without complexing agents. Addition of the complexing agents induced growth of elongated grains of 5-10 ?m in average length. The Tc enhancement was discussed in terms of changes in hole concentration and sample microstructure as a result of use of the complexing agents. 2008 Asian Network for Scientific Information.